The impact exerted by changes of the NBP interest rates on the exchange rate of the Polish zloty - Pronobis, Michał; Sokołowska, Katarzyna (Wpływ wywierany przez zmiany stóp procentowych NBP na stopy procentowe polskiego złotego, 2018)
The aim of the article is to analyse the impact exerted by changes of the NBP base interest rates on the exchange rate of the Polish zloty and to evaluate whether the observed impact is consistent with the theory. A typical assumption grounded in the theory of economy refers to a positive direction of the impact exerted by changes of interest rates stated by the central bank on the exchange rate of the national currency. The analysis covers the impact exerted by changes of the NBP interest reference rate on the behaviour of the nominal market EUR/PLN exchange rate during the period 2004−2015 (in 2015 the latest change of the NBP interest rates took place). The authors have applied the event study method for analysing the response of the exchange rate in particular periods of time: during one day/five days before the decision, and one day/two days/five days after the decision made by the NBP. The analysis divides the decisions made by the NBP into decisions which met expectations of the market and decisions which were unexpected by the market. The results of the research present a picture of random multidirectional changes of various strength which do not confirm indications stated in the theory of economy, referring to the direction of the impact exerted by the monetary policy on the exchange rate
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 529; s. 270-282
Keywords: exchange rates; interest rates; monetary policy; monetary transmission; event study; kursy walutowe; stopy procentowe; polityka pieniężna; transmisja walutowa; studium przypadku